Comparative study between scan sampling behavioral observations and an automatic monitoring image system on a commercial fattening pig farm - Allueva Molina, Queralt; Ko, Heng-Lun; Gómez, Yaneth; Manteca, Xavier; Llonch, Pol (Frontiers in Animal Science, 2023)
Automation is an important element in modern livestock farming. Image computer analysis is the automation technology aiming to monitor farm animals by recording continuous images. Further analysis can be carried out to assess more precisely and effectively farm animals' welfare.The aim of this study was to determine the applicability of the commercial multi-sensor device (Peek Analytics) developed by Copeeks SAS (France), in comparison to human-based observations used to assess behaviors in pigs, including posture (standing/resting), area within the pen (feeding/drinking/resting/enrichment), and activity level (number of active pigs).Two Peek Analytics (Peek 3 and Peek 4) were installed on a commercial fattening pig farm in Murcia (Spain). Each device recorded data of two pens (39 pigs in four pens in total). Scan sampling was the human-based behavioral observation method used in this study. Data was collected for five consecutive days, in the following intervals: 09:00-11:00, 13:00-15:00, and 16:00-18:00 (30 hours of observation in total). Every pig was observed six times per hour and hence the information analyzed includes 7020 observations (180 observations/pig).2 This is a provisional file, not the final typeset article can be due to different methodologies of recording the activity, rather than due to low accuracy of Peek Analytics.